First grand sacred concert of the Beethoven Musical Society at Temperance Hall, Manayunk, Philadelphia, Pennsylvania, October 27, 1864 (United States; Pennsylvania, 2020)
Advertising handbill for the First grand sacred concert of the Beethoven musical society at Temperance Hall, Manayunk, Philadelphia, Pennsylvania, October 27, 1864. No Beethoven works were included on the program.